THE DIGITALIZATION POLICY IN THE EDUCATION SECTOR: INNOVATION AND ADAPTATION - Indrasari, Meithiana; Wajdi, Muh Barid Nizarudin; Prasnowo, M Adhi; Pamuji, Eko; Winarko, Bagus; Fatadona, Hendra (Journal of Social Political Sciences, 2024)
The digitalization of education has become a critical focus for educational transformation in the 21st century. This study explores the key challenges and opportunities of digitalization, focusing on digital competency among educators, access to infrastructure, and the overall impact on student engagement and learning outcomes. Using a mixed-methods approach, data were collected from 500 educators and policymakers through surveys and interviews. The findings reveal that while digital tools increase student engagement (70% positive impact), significant gaps in educator readiness (47% of vocational trainers reported low digital competency) and unequal access to digital infrastructure—particularly in rural areas (72% reported inadequate access)—hinder the full potential of digital education. Additionally, concerns were raised about the impact on critical thinking and social skills, with 40% of respondents believing the lack of in-person interaction could negatively affect student development. The study concludes that for digital education to succeed, policymakers must address both technological access and human capital development through comprehensive professional development and equitable infrastructure investments.